2022
DOI: 10.1177/1759720x221100300
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 2019 EULAR/ACR classification criteria for systemic lupus erythematosus in ANA-positive Chinese patients

Abstract: Background: The aim of this study was to validate the 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) classification criteria for systemic lupus erythematosus (SLE) in antinuclear antibody (ANA)-positive Chinese patients. Methods: Medical records of all adult patients who attended the rheumatology out-patient clinics between May and September 2019 were reviewed. Patients with ever ANA positive (titre ⩾1:80) were included and evaluated for the fulfilment of the 2019 EULAR/AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The fulfillment of the EULAR/ACR, SLICC, and ACR criteria of these patients was obtained, and their performance for a clinical diagnosis of SLE was compared. 2 The current study was conducted to further explore the relationship between the EULAR/ACR score and organ damage in those judged to be clinical SLE in the validation study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fulfillment of the EULAR/ACR, SLICC, and ACR criteria of these patients was obtained, and their performance for a clinical diagnosis of SLE was compared. 2 The current study was conducted to further explore the relationship between the EULAR/ACR score and organ damage in those judged to be clinical SLE in the validation study.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent validation study of Chinese SLE patients using the attribution rule to the non-SLE controls, we showed that the EULAR/ACR criteria had a similar sensitivity (96.1% vs 97.9%) but slightly higher specificity (95.0% vs 92.5%) when than the SLICC criteria. 2 Several recent studies involving adult and pediatric patients have suggested that the EULAR/ACR classification criteria scores might have prognostic value. These studies reported an association between higher EULAR/ ACR SLE score at diagnosis and organ damage (in particular renal) and reduced survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2019 EULAR/ACR classification criteria for SLE and the SLE Disease Activity Index (SLEDAI) include several serological parameters along with signs, symptoms, radiological features, and histologic and pathological findings for the classification of SLE [ 127 , 128 ]. However, in the absence of concurrent systemic inflammation, these parameters often cannot be used to predict neuropsychiatric disease activity [ 129 ].…”
Section: Investigationsmentioning
confidence: 99%
“…In 2019, the European League Against Rheumatism/American College of Rheumatology endorsed “positive ANA (titer ≥ 1:80 by HEp-2 immunofluorescence)” as an entry criterion for systemic lupus erythematosus (SLE) ( 1 ). This criterion was suitable for SLE classification in patients from south China ( 2 ). Furthermore, patients with SLE exhibit elevated levels of total immunoglobulin G (IgG) and ANA IgG subclasses compared with those with other autoimmune diseases ( 3 ).…”
Section: Introductionmentioning
confidence: 99%